(untitled) (Editora Impacto Científico, 2025)
This article discusses the inclusive curriculum in the context of special education, highlighting its relevance to promoting equity in education. The aim of the research was to analyze how the structuring of a curriculum that respects diversity can contribute to the realization of the educational rights of students with disabilities, global development disorders and high abilities. Based on a bibliographic methodological approach, up-to-date and relevant academic productions in the area of inclusive education were consulted, with a view to building a theoretical framework to support the reflections made. The study showed that the traditional curriculum, still centred on a homogenizing logic, excludes or limits the learning possibilities of many students who fall outside the expected standard. Effective inclusion requires the adoption of pedagogical and curricular practices that are flexible, accessible and capable of valuing the uniqueness of each student, recognizing diversity as a constituent element of the school environment. The results obtained indicate that an inclusive curriculum should be thought of as an instrument for guaranteeing rights and overcoming the attitudinal, physical, pedagogical and social barriers present in educational institutions. Analysis of the sources revealed that school inclusion is not limited to the physical presence of students with disabilities in the regular classroom, but implies their effective and meaningful participation in school activities. The conclusion is that the development and implementation of an inclusive curriculum is fundamental to ensuring quality education for all, in line with democratic principles, current legal frameworks and international commitments. The research reaffirms the need for public policies committed to teacher training, collaborative curriculum planning and the adoption of resources that favor the learning of all students, regardless of their conditions or characteristics.